2005
DOI: 10.1021/ma047534v
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Degree of Branching: Preparation of Poly(ether ester)s via Copolymerization of Poly(ethylene glycol) Oligomers (A2) and 1,3,5-Benzenetricarbonyl Trichloride (B3)

Abstract: A novel approach to tailor the degree of branching of poly(ether ester)s was developed based on the copolymerization of oligomeric A2 and B3 monomers. A dilute solution of poly(ethylene glycol) (PEG) (A2) was added slowly to a dilute solution of 1,3,5-benzenetricarbonyl trichloride (B3) at room temperature in the presence of triethylamine to prepare high molar mass gel-free products. PEG diols of various molar masses permitted the control of the degree of branching and an investigation of the effect of the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 64 publications
(169 reference statements)
3
69
0
Order By: Relevance
“…The integral values of dendritic, linear and terminal unit proton resonances of benzene tricarboxylic acid (around d 8.74-8.68 ppm) were used for the estimation. 9,10,25,26 The DB value is found to be 0.52, which agree well with general scale for the hyperbranched polymers made by one-pot procedure. 53 …”
Section: Synthesis Of Photoactive Epoxy Terminated Linear and Hyperbrsupporting
confidence: 81%
See 1 more Smart Citation
“…The integral values of dendritic, linear and terminal unit proton resonances of benzene tricarboxylic acid (around d 8.74-8.68 ppm) were used for the estimation. 9,10,25,26 The DB value is found to be 0.52, which agree well with general scale for the hyperbranched polymers made by one-pot procedure. 53 …”
Section: Synthesis Of Photoactive Epoxy Terminated Linear and Hyperbrsupporting
confidence: 81%
“…7 Limited availability of AB n monomers increases the use of readily available A 2 þ B 3 monomers for the synthesis of HBP. 8,[9][10][11] After preliminary work by Kim 12 on hyperbranched liquid crystalline polymers, (HBLCPs), synthesized by the AB n approach, the revolutionary work in this field was carried out by Percec et al, [13][14][15][16][17][18] Shibaev et al, 19 and others [20][21][22][23] have reported on photo-addressable dendritic polymers (PADLCPs) containing both mesogenic and photochromic groups. PADLCPs have shown enhanced physicochemical properties and photo and thermally induced physical changes as compared with linear polymers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the T g and M n values of OH-terminated polymers with DB ¼ 8% (M n ¼ 14,500 Da, T g ¼ 155 C) and DB ¼ 50% (M n ¼ 17,000 g/mol, T g ¼ 152 C), were close to each other. This finding was also in accordance with that observed previously by Wooley et al [114], where linear, hb, and dendritic polyesters containing an identical amount of phenolic -OH groups per unit showed similar T g values in the range [197][198][199][200][201][202][203][204] C. [117] (continued) Aromatic Hyperbranched Polymers: Synthesis and Application Voit and coworkers [115] prepared hb polyesters by solution polycondensation at room temperature from the previously reported monomer, namely 3,5-bis (trimethylsiloxy)-benzoyl chloride (Scheme 2, 1-2) [109,110]. Fully soluble aromatic AB 2 hb polyesters with a DB of about 55% in very high yield (~98 %) and of high molar mass (M w ¼ 45,000 Da) were achieved, which was in accordance with results previously reported in the literature [79,108].…”
Section: Hyperbranched Poly(aryl Ester)ssupporting
confidence: 93%
“…The authors attributed this to poor chain entanglement of the hb polymers in comparison to the linear analogs. Tailoring the DB through the synthesis of hb poly(ether ester)s was accomplished by Unal et al [117]. The polymerizations were conducted at room temperature using the A 2 + B 3 approach for the reaction of an acid chloride (1,3,5-benzenetricarbonyltrichloride) with poly(ethylene glycol) (PEG) (see Table 1, entry 4 for monomer combination) in the presence of anhydrous triethylamine (TEA) and using chloroform as solvent.…”
Section: Hyperbranched Poly(aryl Ester)smentioning
confidence: 99%
“…[17] Our efforts herein employ PEG as an A 2 oligomer. An A 2 oligomer rather than a monomer permits longer uninterrupted ethylene oxide units for increased chain mobility and possibly increased conductivity.…”
Section: Introductionmentioning
confidence: 99%